Abrasion resistant member containing hard chip and cutter bit using the same
Patent Information
- Application Number
- JP2023127617
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-04
- Publication Date
- 2025-02-17
AI Technical Summary
【0011】 本発明の耐摩耗部材は簡易かつ安価に製造可能であり、本発明の耐摩耗部材は高硬度かつ高耐久で耐摩耗性に優れる。また、本発明の耐摩耗部材をカッタビットに使用した際は優れた耐摩耗性能を長期間発揮することが可能となる。
Smart Images

Figure 2025023473000001_ABST
Abstract
Description
[Technical Field]
[0001] The present invention relates to a hard-tip-containing wear-resistant member and a cutter bit using the same. [Background technology]
[0002] Tunnel construction using methods such as shield tunneling, pipe jacking, and TBM is carried out using tunnel boring machines equipped with cutter bits. Cutter bits are equipped with a carbide tip as the cutting material and a base material that holds the carbide tip at a set angle. Because the base material is made of steel, such as SS or SKC, it is prone to wear when cutting the natural ground. This wear can cause the carbide tip of the cutter bit to fall off the base material. When the carbide tip falls off, the cutting ability of the cutter bit decreases, and a cutter bit without a carbide tip will wear out significantly. In such cases, excavation work must be stopped and the cutter bit replaced, but stopping excavation work hinders the shortening of construction time. Therefore, improvements to the wear resistance of cutter bits are sometimes used to extend their lifespan.
[0003] Therefore, as mentioned above, improving the wear resistance of materials used in cutter bits is a challenge. Traditionally, materials requiring wear resistance include wear-resistant steel plates, cast wear-resistant materials, hardfacing or thermally sprayed coatings, and sintered materials such as cemented carbide and ceramics. The primary material characteristic of a wear-resistant material is evaluated by hardness, and the more wear-resistant a material is, the harder it is. While cemented carbide and ceramics are considered to have the highest wear resistance, these materials are prone to fracture due to their low toughness. Furthermore, because they are bonded to steel or other materials by brazing or adhesive bonding, they are prone to peeling. Meanwhile, cast materials known for their wear resistance, such as high-chromium cast iron and high-manganese cast iron, are widely used as wear-resistant materials, but their wear resistance is inferior to that of cemented carbide and ceramics. In addition, some special wear-resistant materials are also used, such as crushed hard materials such as cemented carbide, which are then combined with welding or casting to form composites. While various wear-resistant materials are available, the main wear-resistant measure for cutter bit base materials is hardfacing. However, even hardfacing has lower wear resistance than carbide tips, so there are limits to how much the base material can be prevented from wearing out.
[0004] In addition to the wear-resistant materials mentioned above, conventional techniques include casting cemented carbide with high-chromium cast iron to create a composite material with cemented carbide, and also using cermets, which have similar material properties to cemented carbide, to create composite materials. Cemented carbide is primarily composed of tungsten carbide (WC), an expensive material due to the use of the rare metal tungsten (W). Therefore, it has been proposed to reuse used insert tips to create cemented carbide for casting.
[0005] Insert tips are the cutting edges of tools used primarily in machining. Materials include cemented carbide, cermet, high-speed steel, and ceramics, with cemented carbide accounting for the majority. Because cemented carbide contains rare metals, it is actively recycled, with used insert tips collected by vendors and recycling companies. Insert tip users rarely separate insert tips by material type; instead, they are collected in a mixed state (cemented carbide, cermet, high-speed steel, and ceramic). After collecting used insert tips, recycling companies sort them by material type. While cemented carbide tips are treated as valuable resources and recycled, cermets are generally disposed of as industrial waste. However, cermets have similar material properties to cemented carbide, being extremely hard and wear-resistant, and their effective use has been considered. Hereinafter, cemented carbide insert tips will be referred to as cemented carbide tips, and cermet insert tips will be referred to as cermet tips.
[0006] As a method for reusing cermet chips, one method has been proposed: crushing the cermet chips to produce crushed cermet particles, mixing the crushed particles with welding material to produce wear-resistant materials, and casting the crushed particles or chips as they are into high-chromium cast iron.Cermet chips are often coated with a material, and bonding coated cermets to high-chromium cast iron is difficult, so the bonding strength could not be maintained.Therefore, improving the bonding strength is important, and conventional technologies exist.
[0007] As a conventional technique for improving the bonding strength, there has been disclosed a technique that enables bonding of the cermet and the substrate by plating the cermet tip, which addresses the problem of fracture due to heat shock when the cermet is cast inside (Patent Documents 1 and 2). However, although such a technique can improve the bonding strength between the substrate and the cermet to some extent, it is considered difficult to use industrially due to the high cost, processing time, and processing man-hours. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Patent Publication No. 2012-86225 [Patent Document 2] Patent Publication No. 2014-83577 Summary of the Invention [Problem to be solved by the invention]
[0009] Therefore, a main object of the present invention is to provide a wear-resistant member having excellent wear resistance, and to provide a cutter bit that can be used for a long period of time by using the wear-resistant member of the present invention. [Means for solving the problem]
[0010] That is, the present invention relates to the following (1) to (5). (1) A wear-resistant component formed by casting a hard tip with high-chromium cast iron and nickel components. (2) The wear-resistant member according to (1) above, characterized in that the content of the nickel component is 0.3 to 10 wt %. (3) The wear-resistant member according to (1) or (2) above, characterized in that the hard tip is a cermet tip. (4) The wear-resistant member according to (1) above, wherein the hard tip has a hard coating removed from its surface by air blasting. (5) A cutter bit characterized in that at least one wear-resistant member according to (1) is provided on the surface of a base material and at least one wear-resistant member is provided on the tip. [Effects of the Invention]
[0011] The wear-resistant member of the present invention can be easily and inexpensively manufactured, and has high hardness, high durability, and excellent wear resistance. Furthermore, when the wear-resistant member of the present invention is used in a cutter bit, it is possible to exhibit excellent wear resistance for a long period of time. [Brief explanation of the drawings]
[0012] [Figure 1] 1 shows a cross-sectional view of a cutter bit according to an embodiment of the present invention. [Figure 2] 1 is a perspective view of a hard tip according to an embodiment of the present invention; [Figure 3] 10A and 10B are cross-sectional views showing a process of fixing a wear-resistant member and a blade material to a base material. [Figure 4] 1A and 1B are diagrams illustrating the progress of wear of a wear-resistant member. [Figure 5] 1 shows a method for fixing a hard tip according to an embodiment of the present invention. [Figure 6] 1 shows a state in which a hard tip according to an embodiment of the present invention is cast-in. [Figure 7] 1 is a cross-sectional view showing a state in which a hard tip is being cast-in according to an embodiment of the present invention. [Figure 8] 1 shows the results of EPMA line analysis of the wear-resistant member of Comparative Example 1 used in the present embodiment. [Figure 9] 1 shows the results of EPMA line analysis of the wear-resistant member of Example 1 used in the present embodiment. [Figure 10] 1 shows the results of EPMA line analysis of the wear-resistant member of Example 2 used in the present embodiment. [Figure 11] 1 shows the results of EPMA line analysis of the wear-resistant member of Example 3 used in the present embodiment. [Figure 12] 1 shows the results of EPMA line analysis of the wear-resistant member of Example 4 used in the present embodiment. [Figure 13] 10 shows the results of EPMA line analysis of the wear-resistant member of Comparative Example 2 used in the present embodiment. [Figure 14] 10 shows the results of EPMA line analysis of the wear-resistant member of Comparative Example 3 used in the present embodiment. [Figure 15] FIG. 2 is a schematic diagram showing a state of a wear test carried out in this embodiment. [Figure 16] 4 shows the results of a wear test on the wear-resistant member used in this embodiment. [Figure 17] 1 shows a backscattered electron image obtained by EPMA analysis of the wear-resistant member of Comparative Example 1 used in this embodiment. [Figure 18] 1 shows a backscattered electron image obtained by EPMA analysis of the wear-resistant member of Example 1 used in this embodiment. [Figure 19] 1 shows a backscattered electron image obtained by EPMA analysis of the wear-resistant member of Example 2 used in this embodiment. [Figure 20] 1 shows a backscattered electron image obtained by EPMA analysis of the wear-resistant member of Example 3 used in this embodiment. [Figure 21] 1 shows a backscattered electron image obtained by EPMA analysis of the wear-resistant member of Example 4 used in this embodiment. [Figure 22] 1 shows a backscattered electron image obtained by EPMA analysis of the wear-resistant member of Comparative Example 2 used in this embodiment. [Figure 23] 1 shows a backscattered electron image obtained by EPMA analysis of the wear-resistant member of Comparative Example 3 used in this embodiment. [Figure 24] 1 shows a photograph of the results of EPMA surface analysis of the wear-resistant member of Example 4 used in this embodiment. [Figure 25] 1 shows a photograph of the results of EPMA surface analysis of the wear-resistant member of Comparative Example 2 used in this embodiment. [Figure 26] 1 shows a photograph of the results of EPMA surface analysis of the wear-resistant member of Comparative Example 3 used in this embodiment. [Figure 27] 1 shows the results of EPMA line analysis of a wear-resistant member made of S25C as a reference example used in this embodiment. DETAILED DESCRIPTION OF THE INVENTION
[0013] In this embodiment, a cutter bit 1 that is fixed to the cutter head of a shield machine and cuts natural ground will be described as an example of the use of the wear-resistant member of the present invention. FIG. 1 shows the cutter bit 1. As shown in FIG. 1, the cutter bit 1 includes a base material 2, a blade material 3 brazed to the base material 2, and a wear-resistant member 4. In this embodiment, silver brazing is used as the brazing material. The base material 2 is a material that is fixed to the excavator (cutter head) and supports the blade material 3, and is a so-called shank material. The base material 2 holds the blade material 3 at a predetermined angle and prevents it from falling off. In this embodiment, the base material 2 is made of a material that has a larger expansion coefficient than the blade material 3 and has sufficient rigidity and strength as a structural member. In this embodiment, SS material, SKC material, etc. are used as the material for the base material 2, but the material for the base material 2 is not limited.
[0014] The front surface 22 of the base material 2 is the surface on the front side in the traveling direction of the cutter bit 1, and as shown in FIG. 1 , it slopes away from the rear surface 24 as it approaches the tip (blade material 3). The back surface 23 of the base material 2 is the surface facing the natural ground (cutting surface) and slopes away from the bottom surface 25 as it approaches the tip (blade material 3). The corner where the extended surface of the back surface 23 intersects with the extended surface of the front surface 22 forms an acute angle. The rear surface 24 of the base material 2 is the surface on the rear side in the traveling direction of the cutter bit 1, and the bottom surface 25 is the surface that abuts against a cutter head (not shown). In this embodiment, the rear surface 24 and the bottom surface 25 of the base material 2 intersect at a right angle. Note that the rear surface 24 and the bottom surface 25 do not necessarily have to be at a right angle. Furthermore, the shape of the base material 2 is not limited. A continuous recess 21 that opens to the tip side is formed on the front surface 22 and the back surface 23 of the base material 2. In this specification, the tip of the base material 2 refers to the corner portion sandwiched between the extended surface of the front surface 22 and the extended surface of the back surface 23 of the base material 2. The recess 21 is a missing portion with a V-shaped cross section formed at the tip of the base material 2. The blade material 3 and the wear-resistant member 4 are fixed (brazed) to the recess 21.
[0015] The blade material 3 is made of cemented carbide and has a rectangular cross section. As shown in FIG. 1 , the blade material 3 is disposed along the extensions of the front surface 22 and the back surface 23 of the base material 2. In this embodiment, the front surface 31 and the back surface 32 of the blade material 3 are exposed at the tip of the base material 2, and the back surface 33 and bottom surface 34 are brazed to the recess 21 (base material 2) or the wear-resistant member 4. The intersections of the front surface 31 and the back surface 32 of the blade material 3 form acute angles. Meanwhile, the intersections of the front surface 31 and the bottom surface 34 of the blade material 3 and the intersections of the bottom surface 34 and the back surface 33 of the blade material 3 form right angles, and the intersections of the back surface 32 and the back surface 33 form an obtuse angle. The cross-sectional shape of the blade material 3 is determined appropriately depending on the shapes of the base material 2 (recess 21) and the wear-resistant member 4, and is not limited to the shape shown in the figure.
[0016] The wear-resistant member 4 is a member in which a plurality of hard tips 5, 5, ... are embedded with their surfaces facing the surface, and as shown in Fig. 1, is brazed to the recess 21 in a state where they are flush with the front surface 22 or the back surface 23 of the base material 2. That is, the plurality of hard tips 5, 5, ... are fixed to the base material 2 in a state where they are flush with the front surface 22 and the back surface 23. The tip end surface of the wear-resistant member 4 in the base material 2 is brazed in a state where it abuts against the bottom surface 34 or the back surface 33 of the cutting material 3. The wear-resistant member 4 may also be fixed to the back surface 24 or side surface of the base material (the surface facing the front or back of the paper in Fig. 1).
[0017] The hard tip 5 of this embodiment is a cermet tip whose main component is titanium carbide or titanium carbonitride, and is a reused tip that has been used as an insert tip. FIG. 2 shows the hard tip 5. As shown in FIG. 2, a through-hole 51 is formed in the center of each hard tip 5 for attachment to a cutting tool or the like. In this embodiment, hard tips 5 having a triangular shape (triangular prism) in plan view are used, but the shape of the hard tip 5 is not limited. The specific gravity of the hard tip 5 is smaller than the specific gravity of the molten metal of the wear-resistant member 4.
[0018] High-chromium cast iron generally refers to an Fe-Cr-C ternary white cast iron containing 7% or more chromium. Due to its high content of hard Cr7C3-type carbides, it is widely used in civil engineering and crushing machinery parts, which are prone to abrasion wear. High-chromium cast iron does not have a JIS standard; the chromium content of commercially available products is limited to approximately 30%, and hardness varies depending on the chromium content. High-chromium cast iron with 25% chromium has a hardness of approximately 700 HV (JIS Z 2244 Vickers Hardness Test - Test Method), while cermets have a hardness of approximately 1700 HV, resulting in a significant difference in the wear resistance of these materials. Therefore, when a cermet (hard tip) is cast into high-chromium cast iron (wear-resistant material 40) to form a wear-resistant component 4, wear progresses from the base of the high-chromium cast iron, as shown in Figure 4. If the bonding strength between the cermet and the matrix is not ensured as wear progresses, the wear of the surrounding matrix will progress, causing the cermet to fall off. If the cermet falls off, only the wear resistance of the high-chromium cast iron will remain, resulting in a decrease in wear resistance. To maximize the wear resistance of the cermet, it is necessary to improve the bonding strength between the cermet and the high-chromium cast iron. A composite material in which the cermet of the present invention is cast into the high-chromium cast iron becomes a wear-resistant member that can maximize the wear resistance of the cermet. In this embodiment, such a composite material consisting of the wear-resistant material 40 and the hard tip 5 is referred to as the wear-resistant member 4.
[0019] The method for manufacturing the wear-resistant member 4 is not particularly limited, and any conventional manufacturing method can be used as long as it involves casting a hard tip (cermet, cemented carbide, etc.) into high-chromium cast iron (wear-resistant material 40). The wear-resistant member 4 manufactured in this manner is fixed to the surface of the base material 2, and the cutting material 3 is fixed to the tip of the base material 2. Figure 3 shows this process. As shown in Figure 3, the wear-resistant member is brazed to the recess 21 of the base material 2. The cutting material 3 is also brazed to the recess 21 and the end face of the wear-resistant member 4.
[0020] Next, the wear-resistant member 4 in this embodiment will be described. The wear-resistant member 4 used in this embodiment is composed of a hard tip 5 and a wear-resistant material 40. In this embodiment, the hard tip 5 is a used cermet tip that has been collected (recycled) and cleaned by air blasting. The purpose of cleaning by air blasting is to remove contaminants such as cutting oil and to remove any coating material applied to the cermet tip. Since the hard coating material must be removed, a silicon carbide-based shot material (hardness: 2400 to 2500 HV, acute-angled shape, particle size: 180 to 425 μm) was used in this embodiment. The shot material does not have to be silicon carbide-based as long as it has a hardness of 2000 HV or more. Note that, although recycled cermet tips are used in this embodiment, the present invention is not limited to this, and unused cermet tips can also be used. Furthermore, although the cermet chips in this embodiment were used with the coating material removed, this is not particularly limited, and cermet chips that have been crushed into particles may also be used.
[0021] A wear-resistant member 4 was fabricated in a mold according to the desired size and shape, and the coating material was removed from the cermet chips. A chip set jig was fabricated by fixing approximately 2 to 20% of the cermet chips (weight of cermet chips / weight of base material) × 100) to a stainless steel round bar and spacers, as shown in Figure 5. The amount of cermet was set to approximately 2 to 20% because approximately 20% was the maximum amount that allowed sufficient circulation of molten metal between the installed cermet chips. In the example, approximately 2% was used, but if the amount of cermet chips that appeared on the wear surface could be increased depending on the application, it is desirable to increase the number of cermet chips within the aforementioned preferred range. When fixing the cermet chips to the stainless steel round bar, spacers were installed so that the gap between the chips was 2 mm or more. The chip set jig was placed in the mold, and the material (molten metal (insertion material) 40) was melted in a high-frequency melting furnace. The molten insert material 40 was poured into the mold at an applicable temperature of 1400 to 1600°C, and the wear-resistant component 4 was cast according to a conventional insert casting method (Fig. 6). When placing the chip set jig in the mold, it is preferable to leave a clearance of about 2 mm between the mold and the chip to allow the molten metal to flow sufficiently. [Example]
[0022] As an example, a chip set jig was fabricated by fixing 21 g of cermet chips, from which the coating material had been removed, with a SUS round bar and spacers in a mold (a φ65 cylindrical sand mold (silica sand-7 wt% water glass)) as shown in Figure 7, and the chip set jig was placed in the mold.The material (molten metal (cast-in insert material) 40) was melted in a high-frequency melting furnace and poured into the mold, and a wear-resistant component 4 was cast at the applicable temperature according to a conventional cast-in insert method. The compositions of the wear-resistant members 4 of Comparative Examples 1 to 3 and Examples 1 to 4 produced in this embodiment are shown in Table 1. Table 2 also shows the results of composition ratios obtained by performing spark discharge optical emission spectroscopy on the wear-resistant materials 4 produced according to the composition ratios in Table 1. [Table 1] [Table 2]
[0023] The insert casting material 40 used in this embodiment was prepared by preparing a molten metal with a predetermined target Cr content using the compounding ratios shown in Table 1. The molten metal was prepared by melting each composition listed in Table 1 in a melting furnace. The insert casting material 40 used in this embodiment was named according to the components and amounts contained. Comparative Example 1 contained approximately 12 wt% Cr and was therefore referred to as 12Cr. Examples 1 to 4 and Comparative Examples 2 and 3 were named 12Cr-0.5Ni, 12Cr-2Ni, 12Cr-4Ni, 12Cr-10Ni, 12Cr-20Ni, and 12Cr-30Ni, depending on the amount of Ni added based on 12Cr. Ni was added by melting 99.97% pure Ni pellets (manufactured by Inco Corporation (now Special Metals Co., Ltd.)) into the insert casting material 40.
[0024] The analysis of the composition ratio of the insert casting material 40 used in this embodiment (shown in Table 2) was carried out by spark discharge optical emission spectroscopy in accordance with JIS G 1253 "Iron and steel - Spark discharge optical emission spectroscopy analysis method" using a measuring instrument named iSPARK 8880 (Thermo Fisher Scientific Co., Ltd.).
[0025] (Bonding strength test) The bond strength between the cermet and the cast-in-place material 40 (high-chromium cast iron) was confirmed by EPMA line analysis. The diffusion bond between the dissimilar materials was confirmed by examining the elemental composition of the dissimilar materials using EPMA line analysis. The thicker the diffusion layer (shown in the graphs for Fe (iron) content in Figures 8–14 (described below)), the stronger the bond strength. To measure the thickness of the diffusion layer at the interface between the cermet and the cast-in-place material (high-chromium cast iron), a specimen (15 mm x 10 mm) was mirror-polished and then analyzed using an EPMA (JEOL JXA-8200 model). The specimen was polished to a mirror finish using a polishing machine (Refine Tech Co., Ltd. APM-128F) with waterproof abrasive paper, starting with #200 and gradually increasing the grit size to #1500. The specimen was then buffed with suede cloth and 1 μm alumina abrasive. The analytical conditions were an acceleration voltage of 15 kV and an analytical current of 50 nA, and eight elements, Fe, Cr, Si, Ni, Ti, C, N, and O, were analyzed.
[0026] Table 3 shows the results of measuring the thickness of the diffusion layer using the wear-resistant members 4 manufactured in Examples 1 to 4 and Comparative Examples 1 to 3. Backscattered electron images (BEI) for Examples 1 to 4 and Comparative Examples 1 to 3 are shown in Figures 17 to 23, and the results of EPMA line analysis are shown in Figures 8 to 14. The backscattered electron images show the analysis lines where line analysis was performed. The thickness of the diffusion layer was measured based on the line analysis results. The vertical axis of the line analysis results indicates X-ray intensity, and the shape of the graph allows the degree of elemental bias to be confirmed. The diffusion layer was measured by focusing on the Fe component, which had the largest difference in X-ray intensity between the matrix and the cermet in the line analysis results. The side with the higher intensity of the Fe component is the matrix, and the side with the lower intensity is the cermet. The part where the intensity of the Fe component suddenly drops is defined as the interface, and the part up to the point where the Fe component becomes almost zero is defined as the diffusion layer. Measurements were performed by reading the scale on the horizontal axis of the graph. [Table 3]
[0027] The results of the X-ray analysis of Examples 1 to 3 show that a diffusion layer is formed from the interface to the cermet side, with a thickness of approximately 400 μm to 500 μm. Within this diffusion layer, the molten metal components Fe, Cr, and Si penetrate into the cermet side, and Ni, the cermet binder, is reduced. This is thought to be causing a replacement of the binder portion. Focusing on the Fe component, the X-ray intensity tends to be low near the cermet interface and increase as it enters the interior of the cermet. In Example 4, the diffusion layer is about 250 μm thick, which is thinner than in Examples 1 to 3, but the bonding strength is superior to that of conventional wear-resistant materials. Also, when focusing on the Fe component, the shape of the X-ray intensity graph inside the diffusion layer is different, and it can be seen that the X-ray intensities of Cr and Si are lower.
[0028] The results of the line analysis of Comparative Examples 1 to 3 show that, like the Examples, a diffusion layer is formed from the interface to the cermet side, but the thickness of the diffusion layer is approximately 110 to 160 μm. As with the Examples, within the diffusion layer, the molten metal components Fe, Cr, and Si penetrate into the cermet side, and Ni, the cermet binder, is reduced. This is thought to be the cause of binder replacement.
[0029] In both the examples and comparative examples, a diffusion layer was formed. This is thought to be because the inclusion of Cr in the molten metal components improved the wettability of the cermet, making it easier for the molten metal to penetrate the cermet. Furthermore, since the inclusion of Ni increased the diffusion layer, it is thought that the inclusion of Ni in high-chromium cast iron further improved the wettability of the cermet, making it easier for the molten metal to penetrate the cermet. For reference, similar experiments to those in the examples and comparative examples were conducted using S25C (carbon steel) as the conventional wear-resistant material 40, and no diffusion layer was formed with S25C (carbon steel).
[0030] Table 3 shows that with a Ni content of 0.5%, the diffusion layer is approximately 450 μm thick, about four times thicker than with a Ni content of 0%. When the Ni content is between 0.5 and 4%, the diffusion layer is approximately 400 to 500 μm, but at 10% Ni, it shrinks to approximately 250 μm. Increasing the Ni content further to 20% or 30% shrinks the diffusion layer even further, to approximately 110 μm at 30% Ni, the same as with a Ni content of 0%. This shows that even a small amount of Ni has the effect of thickening the diffusion layer, and this effect peaks at Ni contents up to about 5%, after which the diffusion layer tends to shrink even when the Ni content is increased.
[0031] Focusing on the range with low Ni content, increasing the Ni content from 0 to 0.5% increases the diffusion layer from approximately 110 μm to approximately 450 μm. If we consider linear interpolation between these two points, the equation between these two points is Y = 680X + 110 (X: Ni content, Y: diffusion layer), and the diffusion layer between these points is as shown in Table 4. [Table 4]
[0032] Increasing the thickness of the diffusion layer leads to an increase in the diffusion bonded layer in Figure 4, which is thought to result in an improvement in the bonding strength between the cermet (hard tip 5) and the high-chromium cast iron (wear-resistant material 40: matrix). This makes it possible to prevent the cermet (hard tip 5) from falling off, resulting in improved wear resistance as a wear-resistant component.
[0033] The results of EPMA area analysis of Example 4 and Comparative Examples 2 and 3 are shown in Figures 24 to 26. In the backscattered electron image (BEI) of Figure 25 for the 20% Ni content (Comparative Example 2), black lumps are observed, and the area analysis of the C content in this area reveals that the C content is high. Therefore, it can be said that graphite has occurred in this area. Furthermore, in the backscattered electron image of Figure 26 for the 30% Ni content (Comparative Example 3), black lumps have also occurred, and this is more pronounced than in the 20% Ni content. The graphite in high-chromium cast iron has a sharp shape and forms brittle parts, which is thought to affect the strength of the material and reduce its wear resistance. In contrast, in the backscattered electron image of Figure 24 for the 10% Ni content (Example 4), it can be seen that almost no black lumps have occurred.
[0034] Abrasion tests are considered as a method for evaluating the wear resistance of metal materials. However, wear phenomena are diverse, the actual phenomenon is complex, and multiple mechanisms may act simultaneously, making it difficult to perform abrasion tests that match the actual phenomenon. If abrasion tests are not performed that match the actual phenomenon, the test results will be completely meaningless, so ultimately, evaluations are often performed based on the actual phenomenon. However, since evaluations based on the actual phenomenon are often very difficult, in practice, the hardness of the material is measured as an index of wear resistance as a guideline for evaluating wear resistance. Therefore, hardness measurements were performed on each of the examples and comparative examples.
[0035] Hardness measurements were carried out using a Vickers hardness tester (VK-M manufactured by Matsuzawa Seiki Co., Ltd.) (JIS Z 2244 Vickers hardness test - Test method). The load was 1 kgf and the loading time was 10 seconds, with measurements taken at 5 points and the average value calculated. The results for the matrix are shown in Table 3. The hardness measurement results show that when the Ni content was 0% and 0.5%, the hardness was around 540 HV, and when it reached 2%, it rose to around 640 HV, and when it exceeded 4%, it tended to gradually decrease, and when it reached 30%, it was quite soft at around 250 HV.
[0036] If the Ni content exceeds 20%, the diffusion layer will be 200 μm or less, resulting in results equivalent to when no Ni is included. It is also believed that graphite will be generated in the matrix, reducing wear resistance. This can be seen from the fact that the hardness of the matrix drops significantly to about 250 HV when the Ni content is 30%. Therefore, the upper limit for the Ni content was set at 10%, which results in a diffusion layer thickness of 250 μm and a matrix hardness of about 470 HV. The lower limit for the Ni content was set at 0.3%, calculated from the diffusion layer calculation values in Table 4, at which the diffusion layer thickness is 250 μm or more for a 10% Ni content.
[0037] (Abrasion test) For reference, abrasion tests were conducted on Example 1, high-chromium cast iron consisting of 12Cr alone (without hard tip 5), and a hardfacing material used to improve the wear resistance of cutter bits. The abrasion test was an erosion abrasion test using an air blasting device (MY-30C, manufactured by Shinto Kogyo Co., Ltd.). As shown in Figure 15, the abrasion test was conducted by maintaining a constant distance between the sample and the nozzle (projection distance) and spraying shot material from the nozzle at a pressure of 0.5 MPa onto the sample. The shot material used was a silicon carbide-based material (CF60), with a Vickers hardness of 2400 to 2500 HV, an acute-angled shape, and a particle size of 180 to 425 μm. All shot material was replaced with new material for each sample. The test time was 60 minutes, and the impact angle of the shot material was 30°. The dimensions of the measurement sample were 50mm x 50mm x 20mm, and the test surface was ground using a surface grinding device with an 80 grit grinding stone. The test was evaluated by measuring the weight of the sample before and after the test (to the nearest 0.01g), and the difference was taken as the abrasion weight loss. Three test specimens were used for each test, and the average value was calculated for evaluation.
[0038] The wear loss of the hardfacing material was 22.18g, and the wear loss of the high chromium cast iron without the cermet tip cast in was 21.59g, which is almost the same, so it can be said that the wear resistance of these materials is equivalent.On the other hand, the wear loss of the 12Cr-0.5Ni wear-resistant material with the cermet tip cast in was 14.38g, so by casting in the cermet tip, the wear resistance improved by about 1.5 times, resulting in excellent wear resistance. [Explanation of symbols]
[0039] 1 cutter bit 2 Base material 21 Recess 3 Blade material 4. Wear-resistant materials 40 Wear-resistant materials 5 Hard Tip 51 Through hole 6. Mold
Claims
1. A wear-resistant component formed by casting a hard tip with high chrome cast iron and nickel components.
2. 2. The wear resistant member according to claim 1, wherein the nickel content is 0.3 to 10 wt %.
3. 3. The wear resistant member according to claim 1, wherein the hard tip is a cermet tip.
4. 2. The wear resistant member according to claim 1, wherein the hard tip has a hard coating removed therefrom by air blasting.
5. A cutter bit comprising at least one wear-resistant member according to claim 1 on a surface of a base material and at least one wear-resistant member on a tip of the base material.
Citation Information
Patent Citations
Method for internal chill cemented carbide
JP2012086225A
Insertingly casting method of cermet
JP2014083577A